Exposed Intramedullary Fixation Produces Similar Outcomes to Buried Fixation for Acute Pediatric Monteggia Fractures. Issue 3 (3rd March 2023) - Lightdale-Miric, Nina R.; Obana, Kyle K.; Fan, Bensen B.; Padilla, Abigail N.; Lin, Adrian J.; Bennett, James T.; Wren, Tishya A.L.
Abstract : Background: Treatment of acute pediatric Monteggia fractures requires ulnar length stability to maintain reduction of the radiocapitellar joint. When operative care is indicated, intramedullary ulna fixation can be buried or left temporarily exposed through the skin while under a cast. The authors hypothesized that treatment with exposed fixation yields equivalent results to buried fixation for Monteggia fractures while avoiding secondary surgery for hardware removal. Methods: A retrospective review of children with acute Monteggia fractures at our Level 1 pediatric trauma center was performed. Patient charts and radiographs were evaluated for age, fracture type, fracture location, Bado classification, type of treatment, complications, cast duration, time to fracture union, time to hardware removal, and range of motion. Results: Out of 59 acute Monteggia fractures surgically treated (average age 6 y, range 2 to 14), 15 (25%) patients were fixed with buried intramedullary fixation and 44 (75%) with exposed intramedullary fixation under a cast. There were no significant differences between buried and exposed intramedullary fixation in cast time after surgery (39 vs. 37 d; P =0.55), time to fracture union (37 vs. 35 d; P =0.67), pronation/supination (137 vs. 134 degrees; P =0.68) or flexion/extension (115 vs. 114 degrees; P =0.81) range of motion. The exposed fixation had a return to OR of 4.5% (2 out of 44), and the buried fixation returned to the OR for removal on all patients. Conclusion: Exposed intramedullary fixation yielded equivalent clinical outcomes to buried devices in the treatment of acute pediatric Monteggia fractures while eliminating the need for a second surgery to remove hardware, reducing the associated risks and costs of surgery and anesthesia, but had a higher complication rate. Open Monteggia fractures or patterns with a known risk of delayed union may benefit from buried instead of exposed intramedullary fixation for earlier mobilization. Level of Evidence: III.